Ogden and Richards Proposed Theories: A Brief Overlook as a Prominent Reference for the Current Studies - Nelia Gari; Zulkifli Zulkifli; Wella Cisilya Putri; Lana Hasanah (REiLA : Journal of Research and Innovation in Language, 2020)
The purpose of this article is to find out whether the Ogden and Richard theories are still worthy of being a reference for the current situation. This study intended to review the theories that are highly popular in the semantic environment. Ogden and Richard's theory is one of the most popular semantic theories in linguistics. This theory is a very simple theory related to thought/reference, symbol and referent. Besides, this theory is often referred to as a triangle of meaning and a semiotic triangle. Many researchers try to review the Ogden and Richard theory (Theory Triangle) based on the understanding and perspective of the researchers. This study described and compared the similarity and difference between five (5) studies on the triangle of meaning proposed by Ogden and Richard (1923) this study the analysis and employed a comparative study as a qualitative study in nature. This study explored five (5) articles e.g...“Ogden and Richards‟ The Meaning of Meaning and early analytic philosophy, Semantic Triangle and Linguistic Sign, Controversies and Misunderstandings about Meaning: On the reception of Ogden and Richards book, (The Meaning of Meaning), Theories of Semantics; Merits and Limitations, Research on Translation Based on Semantic Triangle Theory”. This study sees that the theory of from Ogden and Richards is still worthy of being a reference until now. The studies being used as lens seems giving their positive credits to their study. This means that Ogden and Richards somehow acknowledged being as a prominent study in their field until now.